Islamic spiritual user experience (iSUX) model: a case study of Muslim older adults using Al-Quran mobile application / Nahdatul Akma Ahmad - Ahmad, Nahdatul Akma (2018)
This thesis presents a model which aims to highlight spirituality elements from the perspective of user experience. Despite high profile calls for research in the area of spirituality, the research pertaining spirituality in HCI is still in infancy. Recent literatures discovers most studies focus on design for Islamic spiritual user experience and evaluation of spiritual application for adult users, but fundamental of spirituality and its elements from the view of user experience is limited. Besides, current UX Model did not support designing for Islamic spiritual user experience. This research focused on Islamic spiritual user experience for older adult users while previous research focusing on the adult users. Older adults has been chosen as target user because older adults are more spiritually inclined as they aged. Therefore, there is a need for HCI researchers to understand and identify elements of Islamic spiritual user experience that can be used as guideline in design or evaluation of Islamic spiritual user experience especially for the older adults. The aim of this research is to develop a model for Islamic spiritual user experience based on the older adults. The study employs qualitative method approach within an interpretive paradigm. The Geneva Emotional Musical Scale (GEMS) was adopted as a theoretical lens in order to gain deeper insights on the spirituality elements. A single case study which involved Kompleks Warga Emas (KWE) was conducted to research on the spirituality user experience elements among older adults. The triangulation of qualitative data collection through diary, interviews and observations was done. All data were analyzed by verbatim using thematic analysis. Six themes emerged from the analysis which are effectiveness, efficiency, learnability, satisfaction, sublimity and vitality. These themes are further categorized into 10 attributes; effectiveness (accessibility features), efficiency (simplicity and portability), learnability, satisfaction (attractiveness and reliability), sublimity (transcendence and peacefulness) and vitality (energy and joyful activation). These are embedded into a model called Islamic Spiritual User Experience (iSUX) which are evaluated by the Islamic religious experts, user experience expert and older adult's representatives. The feedback is analysed to help improve the model. Finally, the Islamic Spiritual User Experience (iSUX) Model is hope can increase the understanding of spirituality from the domain of user experience.